Facile route to synthesize polyurethane hollow microspheres with size-tunable single holes - Li, Meng (Langmuir : the ACS journal of surfaces and colloids, 2011)
Synthesis of polymer hollow spheres with single holes has been a challenging task in materials science. In this work, polyurethane (PU) hollow microspheres with size tunable single holes were fabricated through a facile self-assembly-diffusion process. Firstly, the as-synthesized PU polymers were dissolved in chloroform. By adding 10 times volume of water, the PU polymers were self-assembled into micelles in which the chloroform was encapsulated. The PU micelles were then transferred to methanol solution to allow the diffusion of chloroform. The formation of the single holes in shells of the resultant PU hollow spheres was induced by the out-diffusion of the encapsulated chloroform in methanol. By adjusting the diffusion time from 5 to 20 hours, the hole size could be tuned from 75 to 210 nm. The resultant PU hollow spheres with single holes demonstrated high loading efficiency of various guest materials such as nanospheres, nanoparticles, and chemical species, suggesting their promising applications in controlled release, chemical protection, catalysis, and so forth